2023
DOI: 10.3390/life13020590
|View full text |Cite
|
Sign up to set email alerts
|

Altered Language-Related Effective Connectivity in Patients with Benign Childhood Epilepsy with Centrotemporal Spikes

Abstract: Benign childhood epilepsy with centrotemporal spikes (BECTS) is one of the most common childhood epilepsy syndromes and may be associated with language deficits. Resting-state functional magnetic resonance imaging (fMRI) data were collected from a total of 78 children: 52 patients with BECTS (28 drug-naïve and 24 medicated) and 26 healthy controls (HC). Granger causality analysis (GCA) was used to investigate alterations in effective connectivity (EC) between the language network core node (Broca’s area) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The disease involves repeated, intermittent, and unpredictable seizures of the cerebral cortex. While subcortical areas are less studied and understood than the cortex in epilepsy, recent research has shown that they may play a more significant role in some types of epilepsy than previously thought [ 9 ]. For example, some types of focal epilepsy, which originate in a specific area of the brain, may involve subcortical structures in addition to the cortex [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disease involves repeated, intermittent, and unpredictable seizures of the cerebral cortex. While subcortical areas are less studied and understood than the cortex in epilepsy, recent research has shown that they may play a more significant role in some types of epilepsy than previously thought [ 9 ]. For example, some types of focal epilepsy, which originate in a specific area of the brain, may involve subcortical structures in addition to the cortex [ 10 ].…”
Section: Introductionmentioning
confidence: 99%